Natural Disasters Effects, Recovery plans and mechanisms (Latakia University Journal - Economic and Legal Sciences Series, 2023)
Natural disasters lead to severe consequences affecting human life and well-being, destroying physical capital, and leading to loss of financial resources. A disaster with direct damage at the micro-economic level, such as loss of life and property, leads to accumulated damage at the macro-economic level, such as a decline in economic output and production, which affects the country's long-term economic growth and other matters. The recovery process requires steps and stages of time, some of which may be long, and recovery has many challenges, most notably focusing on the quality of recovery. The study sought  to address and measure the effects of natural disasters, and to review obstacles and recovery steps with the aim of developing a short, medium and even long term vision of the reality in Syria after the earthquake of February 6, 2023. The study reached several conclusions, the most important is that we must focus on the quality and speed of recovery and set clear steps for the recovery process.